HEALTH CONDITIONS LINKED TO AGE-RELATED MACULAR DEGENERATION ASSOCIATED WITH DARK ADAPTATION. Issue 6 (June 2018) - Laíns, Inês; Miller, John B.; Mukai, Ryo; Mach, Steven; Vavvas, Demetrios; Kim, Ivana K.; Miller, Joan W.; Husain, Deeba
Abstract : Purpose: To determine the association between dark adaption (DA) and different health conditions linked with age-related macular degeneration (AMD). Methods: Cross-sectional study, including patients with AMD and a control group. Age-related macular degeneration was graded according to the Age-Related Eye Disease Study (AREDS) classification. We obtained data on medical history, medications, and lifestyle. Dark adaption was assessed with the extended protocol (20 minutes) of AdaptDx (MacuLogix). For analyses, the right eye or the eye with more advanced AMD was selected. Multivariate linear and logistic regressions were performed, accounting for age and AMD stage. Results: Seventy-eight subjects (75.6% AMD; 24.4% controls) were included. Multivariate assessments revealed that body mass index (BMI; β = 0.30, P = 0.045), taking AREDS vitamins (β = 5.51, P < 0.001), and family history of AMD (β = 2.68, P = 0.039) were significantly associated with worse rod intercept times. Abnormal DA (rod intercept time ≥ 6.5 minutes) was significantly associated with family history of AMD (β = 1.84, P = 0.006), taking AREDS supplements (β = 1.67, P = 0.021) and alcohol intake (β = 0.07, P = 0.017). Conclusion: Besides age and AMD stage, a higher body mass index, higher alcohol intake, and a family history of AMD seem to impair DA. In this cohort, the use of AREDS vitamins was also statistically linked with impaired DA, most likely because of an increased severity of disease in subjects taking them. Abstract : Cross-sectional study, analyzing the association of dark adaption with several medical conditions, in patients with age-related macular degeneration and controls. Besides age and age-related macular degeneration stage, a higher body mass index, higher alcohol intake, family history of age-related macular degeneration, and possibly AREDS vitamins, seem to be linked with impaired dark adaption.